Domesticating the Child: Maternal Responses to Hereditary Discourse in The Tenant of Wildfell Hall - Pellerito, Elizabeth (Romanticism and Victorianism on the Net, 2012)
This article examines the early nineteenth century connections between human, animal and plant by placing Erasmus Darwin’s The Botanic Garden (1791) and The Temple of Nature (1803) in conversation with Anne Brontë’s The Tenant of Wildfell Hall (1848). I argue that the Romantic versions of heredity described in Darwin’s poetry tended to reinscribe traditional gender roles. Brontë’s Tenant, on the other hand, revises earlier notions of heredity and motherhood via Helen Huntingdon, the wife of an alcoholic who tries to prevent her son from activating his genetic taint. By reconfiguring the supposedly natural connections between patriarchal inheritance of the land on the one hand and biological traits on the other, and by reclaiming and reinscribing popular metaphors of breeding, Anne Brontë’s female protagonist creates and attempts to implement a maternalist version of heredity while remaining entrenched within the nineteenth-century cult of motherhood. Whereas the Romantic and romanticized poetry of Erasmus Darwin and his contemporaries’ approach to natural history bestowed human characteristics on plants in order to make their reproduction more comprehensible, The Tenant of Wildfell Hall does the opposite. Without a satisfactory framework in place to express the anxieties surrounding human heredity, Brontë turns the tables on the metaphor and applies the language of breeding and agriculture to a human child. In doing so, she creates an alternate version of heredity based on maternal strength and power rather than one predicated upon patriarchal structures of kinship and economic inheritance.